HOT PHENOL EXTRACTION OF TOTAL RNA FROM Thermoascus aurantiacus AND CHARACTERIZATION OF ITS THERMOSTABLE XYLANASE GENE - Hairul Azman, Roslan; Awang Ahmad Sallehin, Awang Husaini; Ang, Chung Huap (UNIMAS Publisher, 2011)
Total RNA was successfully isolated using hot phenol extraction method. Three bands representing the 18S, 5.8S and 28S rRNA was observed. No heavy smearing was observed in the RNA band patterns, indicating low levels of polysaccharide contamination, when subjected to 1% agarose gel electrophoresis. Genomic DNA was eliminated using DNase I digestion and lithium chloride (LiCl) precipitation. Two-steps reverse transcriptase polymerase chain reaction (RT-PCR) using M-MuLV Reverse Transcriptase and sequence specific primers for xylanase gene, XynA(F) and XynA(R), successfully generated the target amplicon of 500 base pairs (bp). Sequence analysis of the PCR product indicated as partial sequence of Thermoascus aurantiacus xylanase gene (XynA) deposited in the NCBI GenBank with accession number: AF127529.1 and AJ132635.1. Hot phenol extraction is useful for extracting large quantities of total RNA sufficient for complementary DNA (cDNA) synthesis in shorter period of time.